Пліснеський археологічний комплекс - Филипчук, М.А. (Археологія і давня історія України, 2010)
На основі результатів польових археологічних досліджень, отриманих автором за останні десятиліття, а також аналізу джерел, сформованих нашими попередниками, в статті обґрунтовується положення про функціонування комплексу археологічних пам’яток слов’яно-руської та пізньосередньовічної доби. На основе результатов полевых археологических
исследований, которые были получены автором за
последние десятилетия, а также анализа источников, что были созданы нашими предшественниками, в статье обосновывается положение функциональности комплекса археологических памятников
славяно-русской и познесредневековой эпохи. In the article the question of development of Plisnesko
Archaeological Complex of IX—XIII centuries. It
is done on the basis of sources, obtained during XIX—
XX centuries, and also to the authors during 20 years.
An attempt to divide the complex of sights into two
periods is carried out: Slavic (IX—X centuries) and Old
Russian (XI—XIII centuries). To each of them the inherent
model of development. In Slavonic time a city
looked as a policy, that city-state, and during Old Russian
time had a burg structure.